Improved artery–vein separation with acceleration‐dependent preparation for non–contrast‐enhanced magnetic resonance angiography. Issue 3 (17th October 2013) - Priest, Andrew Nicholas; Taviani, Valentina; Graves, Martin John; Lomas, David John
<x xml:space="preserve">Abstract</x> Purpose To compare the use of acceleration‐dependent and velocity‐dependent flow‐preparation for non–contrast‐enhanced magnetic resonance angiography (NCE‐MRA), investigating both image quality and the ability to discriminate between arteries and veins. We develop an acceleration‐dependent NCE‐MRA method known as acceleration dependent vascular anatomy for non–contrast‐enhanced MRA (ADVANCE‐MRA). Methods Acceleration‐dependent and velocity‐dependent images were acquired using a constant and pulsatile flow‐phantom and from the lower legs of six healthy volunteers and one patient with peripheral vascular disease. The volunteer images were assessed both by quantitative signal measurements and qualitative scoring by a radiologist. Results In the phantom, acceleration‐dependent preparation depicted pulsatile but not constant flow, while velocity‐dependent preparation depicted both. In the volunteers and the patient, the velocity‐dependent preparation was unable to separate the arterial and venous signals completely, with some overlap of arterial and venous signals for all acquired flow sensitizations whereas the acceleration‐dependent preparation gave complete artery–vein separation over a wide range of flow sensitizations. Acceleration‐dependent preparation received the best overall qualitative scores for arterial image quality and venous contamination. Conclusion Acceleration‐dependent NCE‐MRA improves arterial image quality and reduces venous contamination, compared with velocity‐dependent NCE‐MRA, and warrants further investigation in patients. Magn Reson Med 72:699–706, 2014. © 2013 Wiley Periodicals, Inc.